Integrating PjBL to foster edupreneurship: A biology innovation module for senior high school - Risti Wiludjeng Muljasari; Nur Kuswanti; Y. Yuliani (University of Muhammadiyah Malang, 2025)
Science curricula often fail to bridge theoretical knowledge with entrepreneurial skills. This research aimed to develop and assess a Project-Based Learning (PjBL)-integrated teaching module designed to foster edupreneurship in biology technology innovation among Senior High School students. This study employed a systematic Research and Development (R&D) approach using the ADDIE model. This article specifically details the analysis, design, and development phases. The module's validation results, assessed by two expert lecturers, indicated it was